2002
DOI: 10.1603/0022-0493-95.6.1119
|View full text |Cite
|
Sign up to set email alerts
|

Method of Application of Tylosin, an Antibiotic for American Foulbrood Control, with Effects on Small Hive Beetle (Coleoptera: Nitidulidae) Populations

Abstract: The method of application of the antibiotic tylosin (Tylan) for control of oxytetracycline-resistant American foulbrood (Paenibacillus larvae White) was tested in honeybee (Apis mellifera L.) colonies. A powdered sugar mixture with tylosin, applied as a dust, was efficacious in eliminating American foulbrood symptoms at a rate of 200-mg Tylan per 20 g of powdered sugar, applied at weekly intervals for 3 weeks. A second method of treatment consisting of Tylan mixed with granulated sugar and vegetable shortening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…In general, small hive beetle control should not overlook the control of other honeybee pests and vice versa. For example, grease/antibiotic patties used to control American foulbrood seem to worsen small hive beetle infestations because larvae readily accept the patties as food Elzen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, small hive beetle control should not overlook the control of other honeybee pests and vice versa. For example, grease/antibiotic patties used to control American foulbrood seem to worsen small hive beetle infestations because larvae readily accept the patties as food Elzen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Even strong colonies of European honeybee subspecies can be taken over and killed by small hive beetles in the US (Sanford, 1998;Elzen et al, 1999a, b). The state most severely affected by the small hive beetle has been Florida (Elzen et al, 2002;Fig. 3) and the damage to local apiculture can be serious (Elzen et al, 2000b).…”
Section: Current Distribution and Pest Status In The Usamentioning
confidence: 99%
See 1 more Smart Citation
“…The EFB-susceptible German black bee (A. mellifera mellifera) was largely replaced with the EFB-resistant Italian bee (A. mellifera ligustica) in the second decade of the 1900s (Voorhies et al, 1933). Early State efforts certainly reduced AFB incidence, however the widespread use of antibiotics (Sulfathiazole in the 1940s and 1950s, Oxytetracycline from the 1950s until the 1990s, and more recently Tylosin tartrate: Haseman and Childers, 1944;Turell, 1974;Elzen et al, 2002) has significantly (and arguably more dramatically) reduced the incidence of bacterial diseases. However, while prophylactic use of antibiotics may prevent disease outbreak, discontinuation of regular antibiotic application often results in disease reoccurrence (Alippi et al, 1999).…”
Section: Bacterial Brood Diseasesmentioning
confidence: 99%
“…Recent field studies have shown that specific formulations of lincomycin 8 and tylosin 9,10 appear to be suitable for controlling infections of OTC-resistant P. l. larvae in honey bee colonies.…”
mentioning
confidence: 99%